Effect of hyperbaric oxygen therapy on liver function during intermittent ischemia - Baldim,Leticia Botigeli (2013)
PURPOSE: To analyze the effects of hyperbaric oxygen therapy on liver function in rats previously subjected to ischemia and reperfusion. METHODS: A randomly distribution of 23 Wistar rats was conducted into three groups: SHAM, animals subjected to surgical stress without restricting blood flow by clamping the hepatic pedicle, IR, rats underwent hepatic vascular occlusion intermittently for two complete cycles of 15 minutes of ischemia followed by 5 min of reperfusion, IR / HBO, rats underwent hepatic pedicle clamping and thereafter exposed to hyperbaric oxygen pressure of 2 absolute atmospheres for 60 minutes. We evaluated liver function through mitochondrial function, determined by the stages 3 and 4 of respiration, respiratory control ratio (RCR) and mitochondrial permeability transition (Swelling). Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were also quantified . We analyzed the results using the Mann-Whitney test and were considered significant all results with p <0.05. RESULTS: There were significant differences between the results of stage 3 in SHAM vs IR group ; of the stage 4 in the groups IR vs SHAM and SHAM vs IR /HBO; of the Respiratory Control Ratio (RCR) in the group IR vs IR / HBO ; of alanine aminotransferase in the groups IR vs SHAM , SHAM vs IR/HBO and IR vs IR / HBO; aspartate aminotransferase in the groups SHAM vs IR and SHAM vs IR / HBO. CONCLUSION: The whole analysis of the mitochondiral function indicators permits us to conclude that the hyperbaric oxygen therapy acted as a protective agent of the mitochondrial function, minimizing the ischemia-reperfusion injury of the hepatic parenchyma.